USING WORDWALL.NET TO IMPROVE STUDENTS’ VOCABULARY SKILLS OF FOURTH GRADERS: KAMPUS MENGAJAR 6 - Zamzam, Vinna Ainu (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Kampus Mengajar is one of the programs initiated by Kementrian Pendidikan, Kebudayaan, Riset, dan Teknologi in the form of "Merdeka Belajar - Kampus Merdeka." Kampus Mengajar aims to assist school administration and improving literacy, numeracy skills, and technological adaptation. Kampus Mengajar 6 program in this study took place at SDN Adikarto 1 Muntilan. This study aimed to improve the vocabulary skills of fourth-grade students using Wordwall.Net and monitor the increase in vocabulary mastery of each student. The reason for conducting this study is that almost all students need help understanding new vocabulary and lack interest in learning English. Therefore, the researcher used Wordwall.Net to achieve the desired goals of both the Kampus Mengajar and this research. This study used the class action research method and data processing using qualitative descriptive techniques. The results were obtained in the pre-cycle with an average of 54.41, while in the post-cycle with an average of 65.33. There was an increase of 10.92, as well as an increase in each student's grade in the first and second cycles.